Environmental parameters, and not phylogeny, determine the composition of extracellular polymeric substances in microbial mats from extreme environments - Blanco, Yolanda; Rivas, Luis A.; González-Toril, Elena; Ruiz Bermejo, Marta; Moreno-Paz, Mercedes; Parro-García, Víctor; Palacín, Arantxa; Aguilera, Ángeles; Puente-Sánchez, Fernando (Science of The Total Environment, 2019)
The ability to establish biofilms is a key trait for microorganisms growing in extreme environments. The extracellular polymeric substances (EPS) present in biofilms provide not only surface attachment, but also protection against all kinds of environmental stressors, including desiccation, salinity, temperature or heavy metal pollution. The acquisition of suitable biofilm characteristics might thus be an important process mediating the adaptation of microorganisms to novel environmental conditions. In this work we have characterized the EPS of 20 phylogenetically diverse biofilms collected in situ from five contrasting extreme environments, including two geothermal areas (Copahue, Argentina; Seltun, Iceland), two cold areas (Pastoruri glacier, Peru; Byers Peninsula, Antarctica) and one extremely acidic river (Río Tinto, Spain). Biofilms were subjected to biochemical characterization, glycan profiling and immunoprofiling with an antibody microarray. Our results showed that environmental conditions strongly influence biofilm characteristics, with microorganisms from the same environment achieving similar EPS compositions regardless of the phylogeny of their main species. The concentration of some monosaccharides in the EPS could be related to environmental conditions such as temperature or heavy metal toxicity, suggesting that in some cases stress resistance can be mediated by specific sugars. Overall, our results highlight the existence of conserved EPS compositional patterns for each extreme environment, which could in turn be exploited to engineer ecological adaptations in genetically modified microorganisms. This work was funded by the Spanish “Secretaría de Estado de Investigación, Desarrollo e Innovación” from the Economy and Competitiveness Ministry (MINECO) grants N° AYA2011-24803, EPS2014-58494-R, ESP2015-69540-R, ESP2014-55811-C2-2, and ESP2014-51989-P. FPS was supported by the MINECO grant CTM2016-80095-C2-1-R.